1973
DOI: 10.1037/h0034736
|View full text |Cite
|
Sign up to set email alerts
|

The uncertain response in detection-oriented psychophysics.

Abstract: The 5s detected tones masked by gaussian noise under forced-choice and non-forced-choice psychophysical methods. The index of detectability, d', was calculated for each procedure under the assumption that failure to respond in non-forced-choice methods is equivalent to a middle-category response on a 3-point rating scale. This assumption was supported by independence of d 1 and the probability of an overt response, P(R), for a range of P(R) of .26-1.0. This result provides a modern answer to the classical ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 7 publications
(7 reference statements)
0
45
0
Order By: Relevance
“…; see Atkinson and Juola, 1971; Shiffrin and Schneider, 1977). Indeed, a 100-year history in psychophysics suggests that gate-keeper processes near participants’ perceptual thresholds are higher-level and metacognitive in psychological character (Boring, 1920; Fernberger, 1914; Watson et al, 1973). The gate-keeper also engenders a qualitative change in behavior and cognition (hesitancy, information seeking, uncertainty responses, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…; see Atkinson and Juola, 1971; Shiffrin and Schneider, 1977). Indeed, a 100-year history in psychophysics suggests that gate-keeper processes near participants’ perceptual thresholds are higher-level and metacognitive in psychological character (Boring, 1920; Fernberger, 1914; Watson et al, 1973). The gate-keeper also engenders a qualitative change in behavior and cognition (hesitancy, information seeking, uncertainty responses, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The rules of stimulus control are different there, animals have difficulty finding adaptive solutions there, animals become minimally informed observers there, and there are not stimuli there on which to ground operants or conditioned reflexes (Boneau & Cole, 1967;Commons et al, 1991;Davison et al, 1985;Miller et al, 1980;Terman & Terman, 1972). The classical psychophysicists agreed that the threshold state is psychologically complex (Boring, 1920;Fernberger, 1914;George, 1917;Thomson, 1920;Watson et al, 1973;Woodworth, 1938). A threshold event is not the clear stimulus signal that can ground a reflexive response.…”
Section: Controlled Decisional Processes In Uncertainty-monitoring Tmentioning
confidence: 94%
“…Interestingly, the scientific study of this paradigm originated in experimental psychology along with quantitative studies of perception [22 -25]; however, these early attempts were found to be too subjective [23,24,26] and were soon abandoned in favour of 'forced choice' tasks to quantify percepts based on binary choices. After nearly a century of neglect, a series of studies by Smith and co-workers [5] reinvigorated the field of confidence judgements using these paradigms in both human and non-human subjects with the goal of placing the notion of subjective confidence on a scientific footing.…”
Section: Behavioural Reports Of Confidence In Humans and Other Animalsmentioning
confidence: 99%